Reduced Degradation of the Herbicide 4-Chloro-2-Methylphenoxyacetic Acid (MCPA) in Soil Induced by the Fungicide Mixture Mancozeb, Metalaxyl-M, and Chlorothalonil Used in Tank Mixtures and Spray Series - Kim Thu Nguyen; Kilian E. C. Smith; Richard Ottermanns; Christiaan Wijntjes; Joost T. van Dongen; Andreas Schäffer (Soil Systems, 2022)
Pesticides are extensively used in agriculture to prevent infestation of crops, control plant-associated diseases and pests, and increase crop productivity. With regards to typical agricultural practice, tank mixing of two or more plant protection products or the subsequent applications of herbicides, fungicides, and insecticides are common application strategies to improve pest control. Our study provides evidence that the fungicide mixture consisting of mancozeb, metalaxyl-M, and chlorothalonil, each applied according to their recommended field rates, retarded the degradation of the phenoxy herbicide 4-chloro-2-methylphenoxyacetic acid (MPCA) in soil. MCPA dissipation times were between 1.6 and 1.9 days without and 2.5–3.5 days with co-applied fungicides. Furthermore, the proportions of extractable residues, non-extractable residues, mineralization, volatile organic compounds, and MPCA metabolism were altered by the fungicide mixture, i.e., considerably lower amounts of the main transformation product of MCPA, 4-chloro-2-methylphenol, were formed. The effects induced by the fungicides persisted throughout the experiment. Our results demonstrate that the current situation of considering individual active substances in the authorization process for plant protection products could lead to a discrepancy in the exposure assessment for humans and the environment. For specifically these cases, this calls into question whether the legally required level of protection is provided.